Islam Khas Indonesia: Metodologi Dakwah Islam Nusantara - Alfriyani Pongpindan (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
At present there is a tendency for Islam to be synonymous with Arabic culture so that being a true Muslim one must become an Arab Muslim represented in the form of, for example, veils, rather short pants, robes, and so on. Muslims should become Muslims who are truly indigenous according to the culture of Indonesia which is very rich and diverse. Basically humans cannot be separated from their culture because that is their identity from generation to generation to embrace Islam does not necessarily leave the characteristic of local culture that has been inherited by their ancestors. Islam in Indonesia was brought by Arab traders peacefully because it was able to adapt to the culture of Nusantara. Before Islam entered Indonesia, animism, dynamism, Hinduism and Buddhism colored the culture of Nusantara. Islam used that culture as a method of preaching to introduce Islam to non-Islamic communities. Islam comes with unique teachings through the concept of monotheism and egalitarianism in the context of societies that worship gods and caste systems in Hindu teachings so that non-Muslims are attracted to Islam. The Nusantara culture used by Islam as a method of da'wah includes: through building art, carving, music, dance, games, rituals, languages, the use of puppets, and so on. Walisongo is the most enthusiastic preacher in using culture as da'wah so that Islam can rapidly on the Island of Java.Keywords: Islam, Nusantara Culture and Da'wah Method.